On the convergence in female participation rates - Yukiko Abe (European Regional Science Association (ERSA), 2016)
Large regional differences exist in female participation across regions within Japan. This paper uses two datasets to show that a significant convergence in female participation took place from 1940 to 2010. Historically, urban areas have had low participation, whereas non-urban areas have had high participation. The participation rate rose steadily and significantly in urban areas and, to a lesser extent in non-urban areas, and as a result, regional differences shrank over time. The microdata from 1982 to 2012 reveal that regional dispersion is large for married women's regular full-time participation in the traditional sector (manufacturing for the less educated and teaching for the highly educated). Compositional changes in demographics and educational attainment explain 74 percent of the convergence for the age 25-39 group, while they explain 40 percent of the convergence for the age 40-54 group. The increase of non-regular employment explains 60 percent of convergence in the latter group. Convergence in married women's regular full-time participation is only observed in the traditional sector (manufacturing and teaching) but not in the new sector (service and retail). Since the compositional change is the major source of convergence for young women's participation, their behavior did not become alike across regions.
Keywords: J21; R12; R23; 330; convergence; region; female participation